Preferred Taxation Methods for Reducing Automobile Prices Without Decreasing Tax Revenues - Memduh Aslan (Maliye Çalışmaları Dergisi)
In terms of legal security and financial stability, financial burdens must be accountable and predictable. However, policy implementations that can rapidly increase public revenue in extraordinary times are only possible through indirect taxes. In order to make quick fiscal policy decisions in Turkey, the President is given the authority to determine the upper and lower limits, mostly with regard to indirect taxes. Short taxation periods can have a rapid impact on tax revenues from policy changes regarding indirect taxes. Cyclical and political conditions are not preferred that permit an increase of the indirect tax burden on basic consumer goods. With regard to the automotive sector, however, automobiles are mainly supplied to the market as imports and are mostly considered to be luxury consumption products. Because of this, increasing the special consumption tax (SCT) on these products is not considered problematic in terms of tax justice. However, SCT increases also increase the cost of automobile ownership. This is not directly affected by an SCT increase but by the increase in the demand for second-hand vehicles, which also causes their prices to rise. The high SCT applied in the automotive sector shows how the effects of capitalization and taxes can be reflected through prices. This situation has led to a continuous increase in automobile prices that has turned them into an investment tool and into a negative externality by causing a decrease in the capital that can be directed from savings toward production. This study discusses how to use the depreciation effect of tax without reducing tax revenues in order to direct savings toward productive investment areas and to reduce car prices.